2019
DOI: 10.30723/ijp.v16i39.101
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of RF power, pressure and substrate temperature on optical properties of RF Sputtered vanadium pentoxide thin films

Abstract: The V2O5 films were deposited on glass substrates which produce using "radio frequency (RF)"power supply and Argon gas technique. The optical properties were investigated by, UV spectroscopy at "radio frequency" (RF) power ranging from 75 - 150 Watt and gas pressure, (0.03, 0.05 and 0.007 Torr), and substrate temperature (359, 373,473 and 573) K. The UV-Visible analysis shows that the average transmittance of all films in the range 40-65 %. When the thickness has been increased the transhumance was decreased f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Whereas the band gap of the SPT samples was found in the range of 2.2 and 2.4 eV, in the case of RF-MS the band gap is significantly wider, with values ranging from 2.82 eV to 2.90 eV at 70.1 nm. Studies that have reported optical bandgap values for RF sputtered V 2 O 5 films on Si reported bandgaps values ranging from 2.5 to 3.3 eV [46][47][48]. The origin of the UV absorption was extensively studied by Meyn et al [49], who reported that the UV light absorption in the oxides can be enhanced by tetravalent vanadium ion V 4+ presence.…”
Section: Optical Measurementsmentioning
confidence: 99%
“…Whereas the band gap of the SPT samples was found in the range of 2.2 and 2.4 eV, in the case of RF-MS the band gap is significantly wider, with values ranging from 2.82 eV to 2.90 eV at 70.1 nm. Studies that have reported optical bandgap values for RF sputtered V 2 O 5 films on Si reported bandgaps values ranging from 2.5 to 3.3 eV [46][47][48]. The origin of the UV absorption was extensively studied by Meyn et al [49], who reported that the UV light absorption in the oxides can be enhanced by tetravalent vanadium ion V 4+ presence.…”
Section: Optical Measurementsmentioning
confidence: 99%